Peran Kepemimpinan Kepala Madrasah dalam Mengintegrasikan Nilai Islam dan Inovasi Pendidikan - Ilham, Muhamad; Irawan, Irawan; Chyril Futuhana Ahmad (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
This study analyzes the role of Islamic leadership in enhancing educational innovation through the integration of managerial, spiritual, and collaborative values ​​in Islamic schools. Using a qualitative literature review method, this study investigates how principals can apply the principles of amanah (trust) and ithqan (trustworthiness) as a basis for professional and ethical management. The results indicate that effective leadership in madrasas requires a balance between spiritual values, managerial competencies, and a collaborative culture that supports educational excellence. Furthermore, this study emphasizes the importance of educational supervision as a strategy for maintaining innovation and continuous improvement in Islamic educational institutions. An Islamic leadership approach that prioritizes integrity, professionalism, and knowledge sharing will foster an innovative and productive environment. Principals, as leaders, are not only responsible for academic success but must also be able to build a harmonious work climate, prioritize ethics, and continuously encourage positive changes in the learning process. Thus, this study contributes to the development of relevant leadership models in the context of Islamic education.